Experience of Patients Who Have Been Introduced with Ventilators in The Intensive Care Unit (ICU) Sumedang Regional General Hospital in 2019 - Wirawan, Nandar; Ifah Hanifah, Ai (Rifa'Institute, 2023)
Introduction: The complexity of the problems experienced by patients who are installed on ventilators, health workers, especially nurses, need to provide comprehensive nursing care and improve caring attitudes in patients with critical l conditions who are attached to ventilators. Objective: This study aims to dig deeper into the experience of patients who have been installed on ventilators in the Intensive Care Unit (ICU) Room of the Sumedang Regional General Hospital in 2019. Method: Design of the research method used is a qualitative method through a phenomenological approach with samples taken purposively. Result and Discussion: Analyst results a theme from the in-depth interview showed that the experiences of patients who have been put on ventilators include: 1) Psychological Responses: linu, feeling stabbed, thirsty, fear, sadness, between conscious and unconscious, added tightness, sleeplessness, feelings of hopelessness, confusion, between believing or not, unable to breathe, anxious, rebelling, nightmares, stinging, itch worried, upset, uncomfortable, tormented. 2) Patient Support: internal support: child and lukewarm, external support: Health workers (nurses). Conclusion: From the research that was found that the expressions of the 3 participants were appropriate and some were not in accordance with the theory / concept of patients who had been put on ventilators. So, a good, honest, and communicative nurse role is needed in meeting the needs of patients who are attached to ventilators holistically and plenary